2010
DOI: 10.1038/nrg2867
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis strategies for association studies involving rare variants

Abstract: The limitations of genome-wide association (GWA) studies that focus on the phenotypic influence of common genetic variants have motivated human geneticists to consider the contribution of rare variants to phenotypic expression. The increasing availability of high-throughput sequencing technology has enabled studies of rare variants, but will not be sufficient for their success since appropriate analytical methods are also needed. We consider data analysis approaches to testing associations between a phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
442
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(446 citation statements)
references
References 140 publications
1
442
1
2
Order By: Relevance
“…It is certainly well recognised that intrinsic forces continually applied by the paraspinal musculature to the vertebral column are high (13,14) . Furthermore, a recent systematic review found some evidence that exercise programmes which target back extensor muscle strength may have modest improvements on kyphosis (15) ; the finding underpins a randomised controlled trial currently underway in California which will evaluate the effectiveness of multimodal spine-strengthening exercise in older adults with hyperkyphosis (16) .…”
Section: Thoracic Spinal Curvature: Heritability and Genetic Correlatmentioning
confidence: 99%
“…It is certainly well recognised that intrinsic forces continually applied by the paraspinal musculature to the vertebral column are high (13,14) . Furthermore, a recent systematic review found some evidence that exercise programmes which target back extensor muscle strength may have modest improvements on kyphosis (15) ; the finding underpins a randomised controlled trial currently underway in California which will evaluate the effectiveness of multimodal spine-strengthening exercise in older adults with hyperkyphosis (16) .…”
Section: Thoracic Spinal Curvature: Heritability and Genetic Correlatmentioning
confidence: 99%
“…However, the high proportion of rare variants across the genome, presence of allelic heterogeneity, and presence of locus heterogeneity can explain additional prevalence of a trait [20]. and does not measure the direction of association [22]. One year later, Li and Leal developed a similar method, the combined multivariate and collapsing method (CMC).…”
Section: Current Methods To Analyze Low Frequency Variationmentioning
confidence: 99%
“…Direct association testing is plausible, but unlikely to be effective in current common study sizes where the total sample size is < 1000 individuals because rare variants will be scarce and contribute small numbers to the analysis which necessitates cautious interpre-tation [45]. It is difficult and extraordinarily expensive to ascertain large enough data sets to acquire sufficient numbers of cases that carry the same causal rare variant and to be able to detect a difference in allele frequency when the MAF is so low [20,21,22,46,47]. Ignoring this limitation with small sample sizes could lead to unstable estimates of rare variant effects on disease and be uninformative [49].…”
Section: Current Methods To Analyze Low Frequency Variationmentioning
confidence: 99%
“…106,107 It could explain why even very large genome-wide association studies have been able to find only a small proportion of the expected number of causative genes. A current challenge is to find this "missing heritability."…”
Section: Major Role For Uncommon Coding Variants In Some Hypertensivementioning
confidence: 99%